If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -1x + 2y = z Reorder the terms: -1x + 4y + 2y = z Combine like terms: 4y + 2y = 6y -1x + 6y = z Solving -1x + 6y = z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. -1x + 6y + -6y = -6y + z Combine like terms: 6y + -6y = 0 -1x + 0 = -6y + z -1x = -6y + z Divide each side by '-1'. x = 6y + -1z Simplifying x = 6y + -1z
| [8+(-4)]-5= | | -8/12-21/12 | | 12+[-5+(-4)]= | | (7/x)-(1/7)=(2/x) | | 3(3x-2)=15 | | 2(3x-5)+6(x-3)=-3(3-5x)+5x-1 | | 2-4(x+3)=4-2(3x+5) | | 2.5=2/s | | -2(-3)-5y=4 | | -2y-42=3(y+1) | | -2/3(6*3-45)-2(3) | | 9x+2x=0x | | 21-u=17 | | 3x^2-4y=7 | | 2/5*15-1=5 | | (6a+1)(5a+2)= | | 5x-(4x+5)=3x-33 | | 441800*8*5/12 | | 992400*8*5/12 | | -16/n=32 | | 7X-3=4+6X | | 3a^2(a^2b^2+b)= | | (8/4)-(15/4) | | 8/4-15/4 | | 3(2x+4)-5= | | 9-16/8 | | 8/4-(15/4) | | -45x^9-30x^7+15x^3= | | 4x^2+48x-128=0 | | 11x^2-24x+12=0 | | 992400*6*12/12 | | -10x+11+4x=-25 |